1973
DOI: 10.1037/h0035508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of instructions to form common and bizarre mental images on retention.

Abstract: The claim that bizarre mental images facilitate recall more than common images was examined by instructing 32 5s to form a bizarre image for each of 24 noun pairs and a common image for each of 24 other pairs. After a 4-min. filler task, each S was given a cued recall test on the entire list of 48 pairs. Contrary to expectations, bizarre images produced no more correct responses than common images. Since bizarre images took longer to form (5.98 sec. vs. 3.94 sec.), it was concluded that common images are in fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
25
2

Year Published

1978
1978
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 5 publications
6
25
2
Order By: Relevance
“…This pattern of results is in keeping with the simple attentional account because an increase in attention to bizarre items would inevitably result in less attention directed to the common items and, thus, in reduced recall of common items. Furthermore, the simple attentional explanation is in keeping with the well-established finding that bizarre information requires longer processing times than does common information (Hauk, Walsh, & Kroll, 1976;Kroll et al, 1986;Kroll & Tu, 1988;McDaniel & Einstein, 1986;Nappe & Wollen, 1973). Despite these consistencies, however, the simple attentional account has been subject to criticism based on the use of processing time as a measure of attention.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…This pattern of results is in keeping with the simple attentional account because an increase in attention to bizarre items would inevitably result in less attention directed to the common items and, thus, in reduced recall of common items. Furthermore, the simple attentional explanation is in keeping with the well-established finding that bizarre information requires longer processing times than does common information (Hauk, Walsh, & Kroll, 1976;Kroll et al, 1986;Kroll & Tu, 1988;McDaniel & Einstein, 1986;Nappe & Wollen, 1973). Despite these consistencies, however, the simple attentional account has been subject to criticism based on the use of processing time as a measure of attention.…”
mentioning
confidence: 66%
“…First, as noted by Einstein and McDaniel (1987), several researchers (Hauk et al, 1976;Kroll et al, 1986;Nappe & Wollen, 1973) have demonstrated longer processing times for bizarre information relative to processing times for common information without demonstrating a bizarre recall advantage. Although the lack of bizarreness effects can be explained by the use of cued-recall testing in the earlier studies (Hauk et al; Nappe & Wollen) and verbally complex materials in the more recent study (Kroll et al), the fact remains that all three studies demonstrated increased processing times for bizarre materials without a subsequent recall advantage.…”
mentioning
confidence: 96%
“…However, the results of research on the mnemonic effectiveness of bizarre imagery have been less than consistent. Andreoff andYarmey (1976), De1in (1968), and Webber and Marshall (1978) all found better recall performance with bizarre imagery, while other studies reported equal or poorer recall performance than subjects instructed to imagine common associative scenes (Collyer, Jonides, & Bevan, 1972;Hauck, Walsh, & Kroll, 1976;Kulhavy & Heinen, 1974;Nappe & Wollen, 1973;Senter & Hoffman, 1976;Wollen, Weber, & Lowry, 1972).…”
Section: Texas Tech University Lubbock Texas 79409mentioning
confidence: 99%
“…Some experimental work, however, has tended not to support this principle. Research by Wood (1967), Perensky and Senter (1970), Nappe and Wollen (1973), and Senter and Hoffman (1976) found not only that bizarre imagery was no more effective than common images, but also that subjects required more time to form bizarre than common images. Hauck, Walsh, and Kroll (1976) essentially replicated the Nappe and Wollen experiment with more experienced subjects.…”
Section: Principles Of Effective Mnemotechnic Implementationmentioning
confidence: 99%